Management practices and technologies for efficient biological sample collection from domestic animals with special reference to Indian field conditions - Gokula Kannan Ragavan; Purushothaman Selvaraj; Dharman Murugesan; Tirumurugaan Krishnaswamy Gopalan; Soundararajan Chinnaiyan; Dhinakar Raj Gopal; Aravindh Babu Ramasamy Parthiban; Karthik Kumaragurubaran; Azhahianambi Palavesam (BMC, 2023)
Abstract Management strategies and the use of advanced technologies are equally important for determining the sample number and sampling frame for successful field sampling for animal disease prevalence studies. The quality of the biological samples collected in the field has a direct bearing on the integrity of the data generated, prevalence estimates and subsequent policy decisions on disease control. Hence, compromising the quality of biological samples collected in the field could potentially undermine the priority setting principles in disease control strategies. Biological samples collected from domestic animals in the field are precious materials and require meticulous planning for sample collection, sample storage in the field, transportation, and storage in the laboratory. Poorly managed field sampling has a significant detrimental impact on the sample quality and quantity and directly affects the accuracy of disease prevalence data. A bad choice of sampling tools, containers, storage and transport all have a negative impact on the integrity of the sample and consequently have an impact on the outcome. Over the last two years, as part of our one health animal sampling work in India, we have observed challenges and opportunities in the field sampling of animals for disease prevalence studies. This paper aims to provide information on management practices and technologies for efficient biological sample collection from the field and ensure that good quality samples are available for testing.